2020
DOI: 10.22146/ijbiotech.42511
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation ability of rat‐mesenchymal stem cells from bone marrow and adipose tissue to neurons and glial cells

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells and can differentiate into neurons and glial cells. In vitro differentiation would be done by the addition of various factors. There remains no comparison for the differentiation of MSCs from rat bone marrow (rBMMSCs) and adipose tissue (rATMSCS) into neurons and glial cells with basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), and brain‐derived neurotrophic factor (BDNF). The aims of this study were to investigate the effect of bFGF, EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Guan et al (2014) also noted that using a mixture of growth factors, including bFGF, EGF, IGF-1, and NT-3, rat MSCs can differentiate into neurons [8]. showed that the addition of bFGF, EGF, and BDNF to the medium induced the differentiation of rat bone marrow MSCs into neurons and glia [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guan et al (2014) also noted that using a mixture of growth factors, including bFGF, EGF, IGF-1, and NT-3, rat MSCs can differentiate into neurons [8]. showed that the addition of bFGF, EGF, and BDNF to the medium induced the differentiation of rat bone marrow MSCs into neurons and glia [19].…”
Section: Discussionmentioning
confidence: 99%
“…The immunocytochemistry staining to identify the neural-induced rat MSCs was conducted on day 14. The staining protocol was adopted by Noviantari, et al (2020) [19]. The culture medium was removed from the well-plate, then rinsed with PBS twice.…”
Section: Immunocytochemistry Staining To Identify the Neural-induced ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The coverslip was closed with a slide for further observa tion with a light microscope (Noviantari et al 2020).…”
Section: Immunocytochemical Test Against P53 Bcl-2 and Caspase-9 Prot...mentioning
confidence: 99%